The utility of pulmonary function testing in the preoperative risk stratification of patients undergoing transcatheter aortic valve replacement. Issue 6 (16th July 2019) - Pino, Jesus E.; Shah, Varun; Ramos Tuarez, Fergie J.; Kreidieh, Omar I; Donath, Elie; Lovitz, Lawrence. S; Rothenberg, Mark; Cubeddu, Roberto J; Nores, Marcos E; Chait, Robert
Abstract: Background: The role of pulmonary function testing (PFT) as a predictor of clinically relevant endpoints in transcatheter aortic valve replacement (TAVR) is unclear. Objective: To determine the utility of PFT in the preoperative risk stratification of patients undergoing TAVR. Methods: An evaluation of PFT (i.e., FEV1), arterial blood gases (i.e., PO2), the diagnosis of chronic obstructive lung disease (COPD) by the Global Initiative for COPD (GOLD), and the diagnosis of chronic lung disease (CLD) by the Society of Thoracic Surgeons (STS) was performed to determine whether a relationship exists among these parameters and clinically relevant outcomes, including all‐cause 30‐day and 1‐year mortality. Results: A total of 513 patients underwent TAVR between March 2013 and December 2016. Per STS criteria, 269/513 (52%) had CLD with a mean FEV1 of 55.4 ± 12%. Per GOLD criteria, 158/513 (30%) of patients had COPD with a mean FEV1/forced vital capacity of 61.8 ± 8.2%. The severity of CLD was affected by changes in ejection fraction, albumin, creatinine, and B‐type natriuretic peptide levels ( p = .009, p < .001, p < .001, and p < .001, respectively), whereas the severity of COPD was not affected by these same variables, ( p = .302, .079, .137, and .102, respectively). An increased A‐a gradient ( p = .035), increased PCO2 ( p = .016), and decreased PO2 ( p = <.001) demonstrated increased risk of 30‐day mortality. Neither classification (COPD or CLD), nor PFT changes, showed association with 30‐day and 1‐year mortality ( p = NS). Conclusion: This study suggests that isolated abnormalities in spirometry are a poor indicator of clinically relevant outcomes in TAVR. When classified correctly, COPD does not predict clinically relevant postoperative outcomes.